2013
DOI: 10.1016/j.biopsych.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Histone Deacetylase2–Mediated Histone Modifications and Synaptic Plasticity in the Amygdala Predisposes to Anxiety and Alcoholism

Abstract: Background Epigenetic mechanisms have been implicated in psychiatric disorders, including alcohol dependence. However, the epigenetic basis and role of specific histone deacetylase (HDAC) isoforms in the genetic predisposition to anxiety and alcoholism is unknown. Methods We measured amygdaloid HDAC activity, levels of HDAC isoforms and histone H3 acetylation in selectively-bred alcohol-preferring (P) and -nonpreferring (NP) rats. We employed HDAC2 siRNA infusion into the central nucleus of amygdala (CeA) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
203
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(213 citation statements)
references
References 71 publications
10
203
0
Order By: Relevance
“…This is further supported by recent findings that TSA treatment during withdrawal after chronic ethanol exposure corrected the deficits in H3-K9 acetylation by blocking the upregulation of HDAC activity in the amygdala and prevented the development of anxietylike behaviors in rats (Pandey et al, 2008). Furthermore, it has been shown that knockdown of HDAC2 in the central nucleus of amygdala attenuated alcohol intake in alcoholpreferring rats (Moonat et al, 2013). The current report is the first of which we are aware demonstrating that in vitro administration of an HDACi can reverse the effects of in vivo ethanol treatment.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…This is further supported by recent findings that TSA treatment during withdrawal after chronic ethanol exposure corrected the deficits in H3-K9 acetylation by blocking the upregulation of HDAC activity in the amygdala and prevented the development of anxietylike behaviors in rats (Pandey et al, 2008). Furthermore, it has been shown that knockdown of HDAC2 in the central nucleus of amygdala attenuated alcohol intake in alcoholpreferring rats (Moonat et al, 2013). The current report is the first of which we are aware demonstrating that in vitro administration of an HDACi can reverse the effects of in vivo ethanol treatment.…”
Section: Discussionsupporting
confidence: 72%
“…The few studies performed with respect to HDAC-induced histone deacetylation in response to alcohol administration have focused on the forebrain (Pandey et al, 2008;Moonat et al, 2013;Sakharkar et al, 2012). In particular, changes in histone acetylation associated with drug abuse have centered on the amygdala (Pandey et al, 2008;Sakharkar et al, 2012) and the NAc (Renthal and Nestler, 2009b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Kushner et al (2011) and Kushner et al (2012a) support the hypothesis that the same sensitivity to allostatic dysregulation in the brain's stress and affect response systems (e.g., sympathoadrenal-medullary complex) could render individuals vulnerable to both the development of internalizing disorders and the development of dependence on multiple substances of abuse. Along these same lines, several recent articles fi nd overlapping neurobiological structures and processes underlying a variety of psychiatric disturbances and substance dependence (McElligott et al, 2013;Moonat et al, 2013;Saal et al, 2003). In fact, an entire recent issue of the National Institute on Alcohol Abuse and Alcoholism's journal Alcohol Research: Current Reviews (34[4], 2012) was devoted to the association of neurobiological stress systems to the use of alcohol and development of dependence.…”
Section: How Many Comorbidity Models Do We Need?mentioning
confidence: 99%
“…By using histone deacetylase inhibitors, Sakharkar et al (2012) showed in alcohol-preferring P rats that a rapid tolerance is produced to this anxiolytic effect during chronic ethanol treatment via possible epigenetic changes causing a reduction in NPY expression. It is quite possible that these epigenetic changes are far more frequent and affect the transcription of many genes important for plasticity (Nestler, 2014) and that epigenetic mechanisms can also contribute to genetic vulnerability to increased alcohol consumption, at least in animal models (Moonat et al, 2013).…”
Section: Ethanol Administered In Vitro Enhanced Ipsps Andmentioning
confidence: 99%